A Matter of Appearances: How Corporate Leaders Manage the Impressions of Financial Analysts about the Conduct of Their Boards - Westphal, James D.; Graebner, Melissa E. (Academy of Management Journal, 2010)
Our theory and findings suggest that relatively negative stock analyst appraisals prompt corporate leaders to increase externally visible dimensions of board independence without actually increasing board control of management. We also consider how relatively negative analyst appraisals may prompt impression management in CEO communications with analysts, whereby CEOs attest to their boards' tendency to monitor and control management on behalf of shareholders. We also find that increases in formal board independence, in combination with verbal impression management directed toward analysts, result in more favorable subsequent analyst appraisals of firms, despite a lack of effect on actual board control.